Sistem Informasi Berbasis Web untuk Membantu Kegiatan Tracer Study Program Diploma Institut Pertanian Bogor - Sofiyanti Indriasari (IPB University, 2012)
IPB Diploma Program has alumni that are broadly spread throughout Indonesia. Tracer study is always conducted progressively each year. Other methods conducted include questionaire via post, email, mailing list, graduation ceremony, alumni meeting, etc. By evaluating tracer study, some innovations are needed to increase its activities. Regarding the advancement of web based technology and internet media that has gone significant in Indonesia, one innovation for tracer study is a website facility which can be accessed by alumni, assumed that all alumni have internet access. IPB Diploma Program Tracer Study Information System is built on the basis of web technology. This system is aimed to increase data collectivity and gives out information, in form of report with default format prepared by IPB Diploma Program. This research yields an IPB Diploma Program Tracer Study Information System which already helps alumni and the data collection of user satisfaction. IPB Diploma Program Tracer Study Information System has a feature to show report which makes alumni information and user satisfaction data to be easily obtained. The information shown is in the form of graphic and tabular data. On the other hand, this system is also equipped with alumni searching facility to track whether an alumni has already participated in tracer study activity.Keyword : Information system, tracer study, website facility